Shifts in Planting Date and Change in Length of Growing Season in Yazd Province Under Warmer Climate Conditions - Mansuoreh Kohi; Ebrahim Fattahi; Ebrahim Asadi Oskouei (Nīvār)
Changes in the land biosphere since 1970 are consistent with global warming: climate zones have shifted poleward in both hemispheres, and the growing season has on average lengthened by up to two days per decade since the 1950s in the Northern Hemisphere extratropic. In this research, projected change of growing season length (GSL) and the start date of the growing season over Yazd province are investigated using three GCMs (GFDL, HadGEM and MIROC5) under the RCP8.5 scenario during 2021-2040. The results indicate Yazd province will experience extended GSL in a warmer world. The thermal growing season has been projected to increase owing to the earlier onset of growth in late winter and spring. Therefore, the prolongation of GSL under the RCP8.5 is attributed to earlier onset. Future temperature and precipitation scenarios based on GFDL and HadGEM models under the RCP8.5 scenario show more unfavorable conditions for this province. Because of the sensitivity of agriculture to weather and climate conditions, these impacts can have substantial direct and indirect effects on production and profitability.